2012
DOI: 10.1186/1745-6673-7-11
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus spp isolated from dust microhabitat in Brazilian libraries

Abstract: BackgroundThe Cryptococcus spp is currently composed of encapsulated yeasts of cosmopolitan distribution, including the etiological agents of cryptococcosis. The fungus are found mainly in substrates of animal and plant origin. Human infection occurs through inhalation of spores present in the environment.MethodsEighty-four swab collections were performed on dust found on books in three libraries in the city of Cuiabá, state of Mato Grosso, Brazil. The material was seeded in Sabouraud agar and then observed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 59 publications
1
26
0
2
Order By: Relevance
“…General concerns regarding health from exposures to the pathogenic and toxic properties of fungi were addressed by Lugauskas and Kriktaponis (2004), Maggi et al (2000), Pinheiro et al (2011), andShamsian et al (2006). Long-term fungi and fungal spore exposures can lead to a variety of health problems, including upper respiratory illness (asthma, rhinitic symptoms, broncho-pulmonary conditions, or allergies), skin infections, severe cryptococcal meningitis, and even death in those with chronic lung disease (Dalal, et al 2011;Gambale et al 1993;Karbowska-Berent et al 2011;Leite et al 2012a;Leite et al 2012b;Reis-Menezes, et al 2011;Zielinska-Jankiewicz et al 2008). Only one study interviewed library workers, and the results indicated that a significant proportion (49%) reported asthmatic or rhinitic symptoms and 18 tested positive to fungirelated allergies where the presence of those fungi in the library was laboratory confirmed (Gambale et al 1993).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…General concerns regarding health from exposures to the pathogenic and toxic properties of fungi were addressed by Lugauskas and Kriktaponis (2004), Maggi et al (2000), Pinheiro et al (2011), andShamsian et al (2006). Long-term fungi and fungal spore exposures can lead to a variety of health problems, including upper respiratory illness (asthma, rhinitic symptoms, broncho-pulmonary conditions, or allergies), skin infections, severe cryptococcal meningitis, and even death in those with chronic lung disease (Dalal, et al 2011;Gambale et al 1993;Karbowska-Berent et al 2011;Leite et al 2012a;Leite et al 2012b;Reis-Menezes, et al 2011;Zielinska-Jankiewicz et al 2008). Only one study interviewed library workers, and the results indicated that a significant proportion (49%) reported asthmatic or rhinitic symptoms and 18 tested positive to fungirelated allergies where the presence of those fungi in the library was laboratory confirmed (Gambale et al 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Optimal environmental parameters were suggested at 18Á228C and humidity below 55% (Dalal et al 2011;Shamsian et al 2006). Additionally, public and occupational health hazards could be mitigated through surveillance programs (Leite et al 2012a;Zielinska-Jankiewicz et al 2008). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations